Physiological and sanitary quality of organic tomato seeds treated with clove basil extracts - Araujo, Eduardo Fontes; Mauri, Aldo Luiz; Araujo, Roberto Fontes; Ribeiro Amaro, Hugo Tiago; Henriques da Silva, Derly José; Fernandes dos Santos Dias, Denise Cunha (Comunicata Scientiae, 2018)
The seed treatment provides disease control before the crop installation, minimizing the pathogens control cost. However, there are few seed treatment alternatives to organic farming. In this sense, the objective of the study was to evaluate the physiological and sanitary quality of organic tomato seeds treated with clove basil extract. The experiment was carried out in a completely randomized design with a 2x5 factorial (extract concentrations x imbibition periods) for each seed lot. Six lots of tomato seeds produced under organic cultivation were used. The samples of the lots were stored in glass pots in a cold room at 16 ºC and 80% of relative humidity for 12 months. Seeds were treated with clove basil extract at concentrations of 5 and 10% for 0; 2.5; 5; 7.5 and 10 minutes. The seeds physiological and health quality were evaluated by the following tests: moisture content, germination, first count of germination, seedling emergence, emergence speed index and seed health. In general, the wild basil extract does not affect the physiological quality of tomato seeds. There were inhibitory and antifungal activity of Aspergillus sp. using basil extract, significantly reducing their impact on the seeds, for all evaluated factors. It was concluded that the clove basil extract inhibit the Aspergillus sp. incidence in organic tomato seeds, maintaining its physiological quality.